1997
DOI: 10.1016/s0022-5223(97)70144-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of bronchiolitis obliterans syndrome after lung transplantation

Abstract: Several risk factors were associated with the development of chronic allograft dysfunction, which, in turn, had a significant impact on long-term survival. Early identification of lung allograft recipients with risk factors for the development of bronchiolitis obliterans syndrome may allow modification in immunosuppression and antiviral therapy to potentially decrease the prevalence of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
126
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(140 citation statements)
references
References 18 publications
10
126
1
3
Order By: Relevance
“…The lack of effect of graft ischaemic time, recipient sex, and recipient age upon development of primary graft failure has been reported by other groups, although it has been suggested that there is a time threshold for graft ischaemic time beyond which acute lung injury is more likely to occur [17,18]. Subsequent development of BOS has been related to early acute rejection, and no operative factors have been identified as risk factors for the development of this condition [19,20].…”
Section: Discussionmentioning
confidence: 94%
“…The lack of effect of graft ischaemic time, recipient sex, and recipient age upon development of primary graft failure has been reported by other groups, although it has been suggested that there is a time threshold for graft ischaemic time beyond which acute lung injury is more likely to occur [17,18]. Subsequent development of BOS has been related to early acute rejection, and no operative factors have been identified as risk factors for the development of this condition [19,20].…”
Section: Discussionmentioning
confidence: 94%
“…Immunologic factors suggested to have a role in the development of BOS include acute rejection, 25,26 lymphocytic bronchitis, 27,28 HLA mismatch [29][30][31] and CMV pneumonitis, 8,[32][33][34] and non-immunologic factors include ischemia, 30 donor age 35 and recipient age. 36 In the present study we found that infections, an indication for transplant of emphysema, and female recipient status were also independent predictors of earlier development of BOS2, whereas female recipient status was associated with earlier onset of BOS3.…”
Section: Discussionmentioning
confidence: 99%
“…Although early reports linked allograft invasive CMV pneumonitis (CMV-P) to an increased risk for BOS, the strongest evidence of this association comes from the preprophylaxis era (3,4). Small retrospective studies indicated that routine use of ganciclovir for CMV prophylaxis perioperatively decreased CMV disease and delayed the onset of BOS as compared with no prophylaxis (5,6).…”
mentioning
confidence: 99%